Effect of Some Factors on Carcass Traits of Nigerian Sheep Breeds (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study assessed the influence of breed, sex, and location on carcass traits of Nigerian sheep (Yankasa, Uda, Balami).A total of 126 sheep were sourced from abattoirs in Gombe, Yobe, and Borno States. Carcass traits evaluated included hot carcass weight (HCW), neck weight (NW), shoulder weight (SHW), rack weight (RckW), breast weight (BrstW), leg weight (LgW), and loin weight (LnW). Data were analyzed using analysis of variance (ANOVA). The results showed clear effects of breed, sex, and location on carcass traits. Sheep from Borno State consistently exhibited higher values for most carcass parameters, followed by those from Yobe and Gombe. Among the breeds, Balami sheep outperformed Uda and Yankasa in nearly all measured traits across all locations. Males also showed higher carcass values than females within each breed. Notably, Balami rams from Borno State recorded the highest carcass weights across most traits, including HCW, NW, SHW, RckW, LgW, and LnW. In contrast, the lowest values were observed in Yankasa ewes from Gombe State. The findings highlight significant interactions between breed, sex, and location, emphasizing the importanceof considering these factors in sheep breeding and meat production strategies.